Environmental Management Accounting and Environmental Performance Assessment (Institutional Analysis) - Siskawati, Eka; Sukoharsono, Eko Ganis; Rosidi,; Ghofar, Abdul; Manurung, Daniel T. H. (Journal of Environmental Accounting and Management, 2026)
The research objective is to understand changes in management accounting and environmental performance assessment (institutional analysis), which play a role in preparing the company’s environmental report. This study discusses the company’s response when there are changes in government regulations relating to reporting environmental performance. Regulations on reporting environmental performance are categorized into phase 2, namely phase 1 environmental reporting, environmental impact analysis (AMDAL)and reporting on environmental performance phase2, Corporate Performance Rating Program(PROPER). Phase 1 environmental reporting (AMDAL) includes reports of basic activities on the proﬁle of company activities, potential impacts and environmental damage caused and steps to preventthem. Meanwhile, environmental reporting phase 2 (PROPER), includes reports of activities that are beyond compliance, namely the design of internal environmental management systems and corporate relations with external social communities. The regulation on phase 2 environmental performance assessment(PROPER) is compulsory and limited, and this study discusses the motivation behind the company’sresponse to the environment. This study uses a descriptive qualitative approach to explain the role of environmental management accounting in reporting the company’s environmental performance. Data collection methods through interviews and observations were analyzed using case studies and institutionalist theory analysis framework. The results of this study are not intended to be generalized. Therefore,the discussion and research ﬁndings are more contextual. This research was conducted on the company Tango Company, a national company owned by the Indonesian government engaged in mineral processing(cementproduction). The ﬁndings of this study are that environmental management accounting practices at Tango Company involve planning environmental activities and measuring environmental performance in accordance with the assessment criteria expected by the government. The practice of environmental management accounting began to be seen since the government imposeda stage 2 environmental performance assessment.